A Simple Liquid-Liquid Fractionation (LLF) Method for Isolating Deoxyandrographolide dan Andrographolide from Herbs of Andrographis paniculata (Burm., F) Ness and Its Cytotoxic Activity on 3T3-L1 Preadipocyte Cells - Putri Rachma Novitasari; Novia Tri Astuti; Suwijiyo Pramono; Raymond Tjandrawinata; Agung Endro Nugroho (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
The main bitter constituents of sambiloto (Androgaphis paniculata (Burm., F) Ness) are diterpene lactones, namely andrographolide and deoxyandrographolide which have been reported to have antidiabetic, cytotoxic, antiatherosclerosis, anti-inflammatory, and antimicrobial activity. There are many studies that performed the isolation of deoxyandrographolide and andrographolide from A. paniculata herbs, but most of them included several steps that make them not efficient. This research was conducted to do an isolation of deoxyandrographolide and andrographolide through liquid-liquid fractionation (LLF) due to its simplicity, low cost, and time efficient. The extraction of deoxyandrographolide and andrographolide from the herbs was carried out using chloroform as the solvent by using Soxhlet apparatus, and LLF was performed to isolate the compounds. The identities of the compounds were confirmed by TLC scanner compared to its standard references. Hence, these present methods were successfully isolated and determined deoxyandrographolide and andrographolide of A. paniculata. The compounds were also showed relatively moderate cytotoxicity on 3T3-L1 cell lines using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt (MTS) assay, with LC50 of deoxyandrographolide and andrographolide; 29.3173 µg/mL and 37.7011 µg/mL, respectively.